The Effect of Youtube-Based Audio-Visual Media on Student Learning Outcomes In Science Learning In Grade IV - Mahendra Juvikar Siregar; Eva Pasaribu; Emeda Thesalonika (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
This study aims to determine the effect of using YouTube-based audiovisual media on student learning outcomes in fourth-grade science learning at SD Negeri 091273 Karang Bangun. This study employed a quantitative approach with an experimental method. This study employed a pre-experimental design with a One-Group Pretest-Posttest approach. Data analysis was quantitative, with the aim of testing the established hypotheses. The study popuation was grade IV of SD Negeri 091273, located in Karang Bangun. The sample in this study was taken from one class used as a One Group class, thus comprising all fourth-grade students. The data analysis technique used in this study was 26 students.The resuts of the study were obtained from student learning outcomes, with an average pretest score of 41.84 and an average posttest score of 89.47. The Effect of Using YouTube-Based Audio Visual Media on Student Learning Outcomes in Science Learning for Grade IV at SD Negeri 091273 Karang Bangun using the Normality test and hypothesis test obtained a value of a significant leve of 0.01 <probability (0.05) and t count = 41.846 > t table = 1.708. So it is concluded that Ho is rejected and Ha is accepted which means